Educational Media Design for Learning Basic Programming in Branching Control Structure Material Using Problem-Posing Learning Model - Syahidi, Aulia Akhrian; Tolle, Herman; Supianto, Ahmad Afif; Hirashima, Tsukasa (Universitas Muhammadiyah Malang, 2019)
Basic programming is one subject that tends to be difficult for students to learn. Along with the development of technology, several researchers have provided solutions to solve this problem, by developing educational games, educational media, interactive learning media, and other auxiliary media. However, on average they have not used or adhered to the syntax of various existing learning models. This study focuses on designing educational media that uses the problem-posing learning model to study the material of branching control structures in basic programming learning which is recommended as a learning medium for vocational high school students. Educational media named TOLSYASUPI-EduMed. We use the highest type of research and development (R&D), the level 4 that we adopted to be adapted into a number of steps that are in line with the needs of this research area. Observation techniques are used as a form of generative research which is a type of user experience research, to explore information before designing a product/application. The side that we highlight here is how the form of educational media design by following the syntax of the problem-posing learning model. Then do an A/B testing which is assessed by experts to choose the best design with results that are type B designs with a percentage of 90.9%. We also state the analysis of the functional aspects of educational media to strengthen the validity of this design idea.